Meeting the review family: exploring review types and associated information retrieval requirements. (20th September 2019) - Sutton, Anthea; Clowes, Mark; Preston, Louise; Booth, Andrew
Abstract: Background and objectives: The last decade has witnessed increased recognition of the value of literature reviews for advancing understanding and decision making. This has been accompanied by an expansion in the range of methodological approaches and types of review. However, there remains uncertainty over definitions and search requirements beyond those for the 'traditional' systematic review. This study aims to characterise health related reviews by type and to provide recommendations on appropriate methods of information retrieval based on the available guidance. Methods: A list of review types was generated from published typologies and categorised into 'families' based on their common features. Guidance on information retrieval for each review type was identified by searching pubmed, medline and Google Scholar, supplemented by scrutinising websites of review producing organisations. Results: Forty‐eight review types were identified and categorised into seven families. Published guidance reveals increasing specification of methods for information retrieval; however, much of it remains generic with many review types lacking explicit requirements for the identification of evidence. Conclusions: Defining review types and utilising appropriate search methods remain challenging. By familiarising themselves with a range of review methodologies and associated search methods, information specialists will be better equipped to select suitable approaches for future projects.